Teaching English as a second language to visually impaired or blind students - Abduvokhidova Shakhribonu Akmalovna (Zien Journals, 2021)
The following article is wrote in order to represent methods, rules and advices to the beginner teachers in the sphere of teaching English as a second language to the Visually impaired or blind students. And also this article might be useful to the parents or the student who studies English by the methods of Self study. It also covered class observation and used a social constructivist framework of disability. The study revealed that the students received inadequate modifications of instruction in foreign language learning. However, the students used a variety of resources with the screen reader technology such as Non Visual Desktop Access (NVDA) and Job Access with Speech (JAWS). These findings suggest that visually impaired students actually can have unique ways of learning foreign language supported by the assistive technology. These abilities should be acknowledged to obtain the perspectives of students who receive disability specific education. Moreover, the study might provide a further facet to the research especially on the importance of learning strategies in special education.
Keywords: IV Learners; students; educators; blind students studying